การสังเคราะห์รูปแบบการศึกษาชั้นเรียนวิชาคณิตศาสตร์ของนักเรียนในระดับการศึกษาขั้นพื้นฐาน A SYNTHESIS OF A MATHEMATICS LESSON STUDY MODEL OF BASIC EDUCATION STUDENTS - ทุมทอง บุญเลี้ยง (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อสังเคราะห์รูปแบบการศึกษาชั้นเรียนวิชาคณิตศาสตร์ของนักเรียนในระดับการศึกษาขั้นพื้นฐาน และเพื่อศึกษาผลการใช้รูปแบบการศึกษาชั้นเรียนวิชาคณิตศาสตร์กับนักเรียนในระดับการศึกษาขั้นพื้นฐานที่สังเคราะห์ขึ้น กลุ่มเป้าหมายแยกเก็บรวบรวมข้อมูลออกเป็น 2 กลุ่มดังนี้ กลุ่มแรกคือ ครูผู้สอน ในสาระการเรียนรู้คณิตศาสตร์ ในระดับช่วงชั้น 3-4 จำนวน 20 คน และกลุ่มที่ 2 คือ นักเรียนในชั้นเรียนที่ครูกลุ่มเป้าหมายแรกสอนอยู่คือ นักเรียนชั้นมัธยมศึกษาปีที่ 1-6 จาก 3 โรงเรียน รวม 90 คน เครื่องมือในการเก็บรวบรวมข้อมูลได้แก่ แบบทดสอบ แบบประเมินและแบบสัมภาษณ์เกี่ยวกับกระบวนการคิดเชิงระบบ การวิเคราะห์ข้อมูลใช้การหาค่าเฉลี่ย ร้อยละ ส่วนเบี่ยงเบนมาตรฐาน การวิเคราะห์โปรโตคอลและการทดสอบที ผลการวิจัยสรุปได้ดังนี้ 1. รูปแบบการศึกษาชั้นเรียนวิชาคณิตศาสตร์ของนักเรียนในระดับการศึกษาขั้นพื้นฐานมี 6 ขั้นตอนที่สำคัญคือ 1.1 ขั้นที่ 1 ร่วมกันจัดตั้งกลุ่มครูที่สอนในวิชาคณิตศาสตร์ 1.2 ขั้นที่ 2 ทำการศึกษาชั้นเรียน 1.3 ขั้นที่ 3 วางแผนการสอนกระบวนการคิดเชิงระบบและการทำวิจัยในชั้นเรียน 1.4 ขั้นที่ 4 สอนและสังเกตการสอนร่วมกัน 1.5 ขั้นที่ 5 อภิปรายและวิเคราะห์ผลการสอนและผลจาการทำวิจัยในชั้นเรียน 1.6 ขั้นที่ 6 สะท้อนผลและวางแผนในเนื้อหาต่อไป 2. ผลการใช้รูปแบบการศึกษาชั้นเรียนวิชาคณิตศาสตร์กับนักเรียนในระดับการศึกษาขั้นพื้นฐานที่สังเคราะห์ขึ้นพบว่า 2.1 คะแนนเฉลี่ยผลสัมฤทธิ์ทางการเรียนรายวิชาคณิตศาสตร์เพิ่มเติมของนักเรียน จำนวน 3 โรงเรียนพบว่า นักเรียนได้คะแนนเฉลี่ยต่ำสุดคิดเป็นร้อยละ 69.21, 69.31 และ 78.21 ได้คะแนนเฉลี่ยสูงสุด คิดเป็นร้อยละ 89.05, 86.63 และ 82.59 โดยนักเรียนทุกคนสามารถผ่านเกณฑ์ที่กำหนดไว้ 2.2 การประเมินความแตกต่างระหว่างคะแนนเฉลี่ยคุณลักษณะในการเรียนและหลังการเรียนรู้โดยใช้สถิติทดสอบที (Paired Samples) พบว่า คะแนนเฉลี่ยคุณลักษณะในการจัดการเรียนรู้ที่ส่งเสริมกระบวนการคิดเชิงระบบหลังเรียนในแต่ละโรงเรียนสูงกว่าก่อนเรียนอย่างมีนัยสำคัญทางสถิติที่ระดับ 0.05 Abstract This purposes of this research were to synthesize a mathematics lesson study model of basic education students, and to examine outcomes of using the synthesized mathematics lesson study model of basic education students. The target population was divided for collecting data into 2 groups: the first group consisted of 20 third-fourth interval class teachers in the mathematics learning strand, and the second group consisted of 90 Mathayomsuksa 1-6 (grades 7-12) students from 3 schools who were in the classrooms being taught by the teachers in the first group. The instruments used for collecting data were a test, an evaluation form, and an interview form on the systematic thinking process. The collected data were analyzed to find out mean, percentage, and standard deviation; using protocol analysis and a t-test. The research finding could be summarized as follows: 1. The mathematics lesson study model of basic education students had the following 6 major stages. 1.1 Stage 1 cooperatively formed a group of mathematics teachers. 1.2 Stage 2 conducted a lesson study. 1.3 Stage 3 planned the systematic thinking process teaching and conducted classroom research. 1.4 Stage 4 taught and observed teaching together 1.5 Stage 5 discussed and analyzed teaching outcomes and the results of conducting classroom research. 1.6 Stage 6 reflected and planned next contents. 2. For the outcomes of using the synthesized mathematics lesson study model of basic education students, the following were found: 2.1 For the mean scores on additional mathematics learning achievement of the students at 3 schools, it was found that the students earned the lowest mean scores at 69.21%, 69.31%, and 78.21% and earned the highest mean scores at 89.05%, 86.63% and 82.59%. All of these students could pass all of the established requirements. 2.2 In evaluating differences between mean scores on learning characteristics and after learning using t-test(paired samples), it was found that the mean score on characteristics of organization of learning which enhanced the systematic thinking process after learning at each school was higher than before learning at the 0.05 level of statistical significance.